Have an eye on the buckled cucumber: An eye tracking study on visually suboptimal foods. (September 2017) - Helmert, Jens R.; Symmank, Claudia; Pannasch, Sebastian; Rohm, Harald
Highlights: Eye tracking in a food choice task comprising eight items. Suboptimal food items were presented among impeccable foods. Studied influence of price badge design on attention towards suboptimal foods. Products with deviating price badge were looked at faster and inspected longer. Choice of suboptimal food items increased by price reductions only. Abstract: Waste is an ever growing problem in the food supply chain, starting in the production up to the consumers' households. A precondition for a consumer to purchase a product is to recognize it as an option in the first place. Therefore, in the present study, we investigated eye movement behavior on impeccable and visually suboptimal food items in a purchase or discard decision task. Additionally, in some trials price badges of the suboptimal food items were designed specifically in order to attract attention. Design changes included messages regarding price and taste, respectively, either presented in red or green. The results show that the design changes indeed attracted attention towards suboptimal food items in terms of time to first fixation, and also prolonged total fixation duration. However, only color yielded differences between the design variations, with red resulting in longer total fixation durations. Additionally, we inspected choice behavior towards visually suboptimal food items. As can be expected, purchase decisions declined for the suboptimal as compared to the impeccable items. However, when presented with differently designed price badges, a positive trend to purchase the suboptimal items was obtained. Our results show that price badge designs impact attention, cognitive processing, and finally also purchase decisions. Therefore, supplying visually suboptimal food in stores should be embedded into efforts to attract attention towards these products, as selling visually suboptimal food might positively impact waste balance in the food domain.